L’autorité éducative : bienveillance envers l’autre, vigilance envers soi - Camille Roelens (Éducation et Socialisation)
The aim of this paper is to address the question of authority in the frame of educational relationships, focusing on the specific vulnerability to which the one successfully occupying an authority position s exposed in the contemporary democratic context. The reflexion, conducted from a philosophical point of view, is articulated around a wide acceptation of the kindness, and in permanent resonance with the double-dealing of individual autonomy and autonomous functioning of collectives, which seems to be the functioning of the individuals’ society. The idea here is to evidence that durably being benevolent to each other when in an authority position requires a certain kindness to oneself, which we refer to as vigilance towards oneself, and which appears to be necessary when authority is considered as a posture of service, influence and accompaniment, rather than a posture of command.